Cover Image. Issue 1 (25th January 2023) - Wagaskar, Vinayak G.; Levy, Micah; Ratnani, Parita; Sullimada, Sharmila; Gerenia, Mae; Schlussel, Kacie; Choudhury, Samia; Gabriele, Marla; Haas, Ian; Haines, Kenneth; Tewari, Ash
Abstract : The cover image is based on the Original Article A SelectMDx/magnetic resonance imaging‐based nomogram to diagnose prostate cancer by Vinayak G. Wagaskar et al., https://doi.org/10.1002/cnr2.1668 . Image Credit: Laura Roy